2007
DOI: 10.1074/jbc.m610550200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Phenotypes of Active Site and Human Autosomal Dominant Progressive External Ophthalmoplegia Mutations in Drosophila Mitochondrial DNA Helicase Expressed in Schneider Cells

Abstract: We report the cloning and molecular analysis of Drosophila mitochondrial DNA helicase (d-mtDNA helicase) homologous to human TWINKLE, which encodes one of the genes responsible for autosomal dominant progressive external ophthalmoplegia. An RNA interference construct was designed that reduces expression of d-mtDNA helicase to an undetectable level in Schneider cells. RNA interference knockdown of d-mtDNA helicase decreases the copy number of mitochondrial DNA (mtDNA) ϳ5-fold. In a corollary manner, overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
71
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(86 citation statements)
references
References 37 publications
13
71
2
Order By: Relevance
“…2A). Even in the uninduced condition, the cells carrying pMt/invLon/ Hy suppressed expression of Lon by >10-fold, most likely due to leaky expression (32)(33)(34)(35). In contrast, expression of β-tubulin was unchanged.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…2A). Even in the uninduced condition, the cells carrying pMt/invLon/ Hy suppressed expression of Lon by >10-fold, most likely due to leaky expression (32)(33)(34)(35). In contrast, expression of β-tubulin was unchanged.…”
Section: Resultsmentioning
confidence: 97%
“…Southern blotting was performed as described previously (32), and the data were analyzed using a PhosphoImager (Molecular Dynamics). Blots were probed with radiolabeled DNAs for the mitochondrial gene Cytb and the nuclear histone gene cluster.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, evaluation of mtDNA copy number in cultured Schneider cells following overexpression of Drosophila mtDNA helicase genes bearing missense mutations suggested that heterohexamers with only one or two mutant subunits retained some helicase activity in vivo (12,42). However, targeted mutations that substantially inactivate catalytic function may prove enlightening in subunit mixing experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The C10orf2 gene product dynamically colocalizes with mtDNA in nucleoprotein structures known as mitochondrial nucleoids (5,9), and knocking down expression of C10orf2 by RNAi results in the rapid decrease in mtDNA copy number in cultured human osteosarcoma (143B) cells (10). Overexpression of catalytic mutants and dominant disease variants of the mtDNA helicase in cultured human or Schneider cells results in stalled mtDNA replication or depletion of mtDNA (11)(12)(13), which emulates the disease state. However, only two of five adPEO mutants exhibited a dominant negative phenotype with mtDNA depletion in Schneider cells (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation